2021
DOI: 10.35459/tbp.2021.000199
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Undergraduate Research to Remote Work to Increase Engagement

Abstract: Demand for undergraduate research experiences typically outstrips the available laboratory positions, which could have been exacerbated during the remote work conditions imposed by the SARS-CoV-2/COVID-19 pandemic. This report presents a collection of examples of how undergraduates have been engaged in research under pandemic work restrictions. Examples include a range of projects related to fluid dynamics, cancer biology, nanomedicine, circadian clocks, metabolic disease, catalysis, and environmental

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This component is ideally available in a recorded and written format to allow students to reference back to it. This is especially important for maintaining the availability of information in a virtual format ( Cohen et al 2021 ).…”
Section: Virtual Expeditions Have Scalable Formatsmentioning
confidence: 99%
“…This component is ideally available in a recorded and written format to allow students to reference back to it. This is especially important for maintaining the availability of information in a virtual format ( Cohen et al 2021 ).…”
Section: Virtual Expeditions Have Scalable Formatsmentioning
confidence: 99%
“…Due to the COVID-19 pandemic, many undergraduates, including those at the University of Washington, spent nearly a full year learning remotely, and undergraduate researchers lost their on-campus work–study research positions. , We set out to re-employ the work–study undergraduate researchers at our Institute by offering a virtual research opportunity, which has been reported to be beneficial and valuable for students in other undergraduate research programs. , However, we needed a different approach than our previous apprenticeship model, as the frequent 1:1 contact central to that model was impractical to implement remotely and too few mentors were free to individually work with each undergraduate at our Institute. Previous cohort-based research courses in computational protein design, in which multiple students are taught by a smaller number of mentors, enabled them to accommodate greater numbers of students and have shown significant success in increasing students’ enthusiasm for biochemistry and computational biology. We adopted this cohort-based model and curated a completely remote computational curriculum that allowed students to take ownership of their portion of a team research project while learning from each other.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 We set out to re-employ the work−study undergraduate researchers at our Institute by offering a virtual research opportunity, which has been reported to be beneficial and valuable for students in other undergraduate research programs. 19,20 However, we needed a different approach than our previous apprenticeship model, as the frequent 1:1 contact central to that model was impractical to implement remotely and too few mentors were free to individually work with each undergraduate at our Institute. Previous cohort-based research courses in computational protein design, in which multiple students are taught by a smaller number of mentors, enabled them to accommodate greater numbers of students and have shown significant success in increasing students' enthusiasm for biochemistry and computational biology.…”
Section: ■ Introductionmentioning
confidence: 99%